Pendidikan Karakter di TK Pertiwi Batang Gansal (Studi Kualitatif) - Wasiah Wasiah; Yuni Resiyati; Supatmi Supatmi (Jurnal Pendidikan Tuntas, 2023)
Character education is moral education, character, values, character that aims to develop the ability of students to make good and bad decisions, as well as maintain the good and realize that goodness in everyday life wholeheartedly, based on the explanation above it is also known that teachers need to provide good character for children. This study uses a type of research with data collection in a natural setting, using natural methods, and conducted by a naturally interested researcher or researcher. In qualitative research, data collection is carried out in natural settings (natural conditions), primary data sources, and data collection techniques. The techniques for collecting this data consist of: Interview, Observation and Documentation. Data analysis is qualitative in nature described by words or sentences separated by category to obtain conclusions. Based on the results of research on "Implementation of character education in Pertiwi Batang Gansal Kindergarten can be implemented well. This can be seen from that child can be honest, disciplined, independent, high curiosity, care for the environment and children can cooperate with their friends both in learning and in playing. It can be explained that the purpose of character education in children is to improve the quality of educational outcomes that lead to the achievement of the formation of character and noble character of students as a whole, integrated, and balanced. Character education in schools is a vital need so that the next generation can be equipped with basic abilities as one of the important characters to live in the era of global information. In order for children to be honest, teachers and kindergarten managers provide honest boxes for children. Keywords: Character Education, internalization, Qualitative Study